2019
DOI: 10.1007/s12640-019-00067-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Isolation Stress Affects Subsequent Crowding Stress-Induced Brain Nitric Oxide Synthase (NOS) Isoforms and Hypothalamic-Pituitary-Adrenal (HPA) Axis Responses

Abstract: The nitric oxide (NO) pathway in the brain is involved in response to psychosocial stressors. The aim of this study was to elucidate the role of nNOS and iNOS in the prefrontal cortex (PFC), hippocampus (HIP), and hypothalamus (HYPO) during social isolation stress (IS), social crowding stress (CS), and a combined IS + CS. In the PFC, 3 days of CS increased iNOS but not nNOS protein level. In the HIP and HYPO, the levels of nNOS and iNOS significantly increased after 3 days of CS. In the PFC, IS alone (11 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 53 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…A previous study demonstrated that stress could increase iNOS levels in the cerebral cortex through the NF-κB pathway (Zlatkovic and Filipovic, 2013). Furthermore, stress caused the overproduction of iNOS-derived NO, which further led to behavioral changes and HPA axis dysfunction (Gadek-Michalska et al, 2019). Based on these findings, it is suggested that PDTC could influence behavioral changes induced by CUMS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A previous study demonstrated that stress could increase iNOS levels in the cerebral cortex through the NF-κB pathway (Zlatkovic and Filipovic, 2013). Furthermore, stress caused the overproduction of iNOS-derived NO, which further led to behavioral changes and HPA axis dysfunction (Gadek-Michalska et al, 2019). Based on these findings, it is suggested that PDTC could influence behavioral changes induced by CUMS.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, NO is a kind of gas molecule that has been reported to play a major role in the pathogenesis of stress-related disorders (Gulati et al, 2015). Evidence is accumulating that chronic stress exposure can cause overproduction of NO, resulting in disruption of hypothalamic-pituitary-adrenal (HPA) axis activity (Gadek-Michalska et al, 2019). The activation of the HPA axis is one of the central physiological mechanisms involved in the stress response (McEwen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overactivation of the insular cortex related with colonic hypersensitivity (19) (Continued) Increased mast cells density (145) In WKY rat activated mast cells, MPO level & transient hyperpermeability, alteration of mitochondrial activity (146) Anxiety-like and depression-like symptoms Early transient changes (Day 3) in the nitrergic expression in the PFC, hippocampus, hypothalamus (147) Social isolation Alterations in the IL-18 pathway and MUC2/TFF3 expression (149) Anxiety-like and depression-like symptoms Reduced BDNF levels & increased reactivity of the HPA axis (148) Changes in the nitrergic expression in the PFC, hippocampus, hypothalamus (147) Abdominal surgery Impaired gastric emptying Low ghrelin concentration (249,251,252) Impaired motility through the activation of the inhibitory reflex pathway increased cytokines expression (TNFa, IL1α, IL6, IL1β, CCL2) (241) infiltration resident macrophages (245) Impaired motility, delayed transit increased cytokines expression in muscular layers (240) 241Increased permeability non-related to TLR2/4 (244) Activation of nuclei (supraoptic nucleus, locus coeruleus, paraventricular nucleus of the hypothalamus & rostral raphe pallidus) expressing nucleobindin2/nefastin complex involved in the decrease of food intake and GI transit (253) 5HT, serotonin; 5HT1A/1B/2A/2B, serotonin receptor type 1A, 1B, 2A, 2B; ACTH, adreno cortico trophic hormone; AMPA, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid; BDNF, brain-derived neurotrophic factor; CCL2, chemokine ligand 2; CRH, corticotropin-releasing hormone; CRHR1 corticotropin-releasing hormone receptor type 1; D1/2/3/4/8/10, day 1/2/3/4/8/10; Eo, eosinophils; GC-C/cGMP, guanylate cyclase C/cyclic guanylin monophosphate; GI, Gastrointestinal; GR, Glucocorticoid receptor; HPA, hypothalamus-pituitaryadrenal; IL, interleukin; MC, mast cell; MPO, myeloperoxidase activity; MUC2, Mucin 2; NMDA, N-methyl-D-aspartate; PFC, prefrontal cortex; SC, spinal cord; SERT, serotonin transporter; TFF3, rail fold factor 3; WKY, wistar kyoto. (29), etc.…”
Section: Stress-related Models Of Fgidmentioning
confidence: 99%
“…Conversely, in the social isolation stress (SIS) model, the animal is isolated from the rest of the cage. Often applied just after the weaning, SIS modifies the development of the brain and influences the nitrergic system in several brain areas such as the hippocampus, the frontal cortex by increasing the nNOS expression in the hippocampus and hypothalamus and iNOS in the prefrontal cortex (147). A decrease production of BDNF, and an activation of the HPA axis which produce more corticosterone.. Mice exposed to SIS, have an impaired reactivity to stress with an overreaction to another stressor together with increased anxiety-and depression-like symptoms (148).…”
Section: Social Stressmentioning
confidence: 99%